1998
DOI: 10.1002/(sici)1521-3773(19980316)37:5<652::aid-anie652>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

A Boron-Bridged Tetrathiaporphyrinogen

Abstract: Lewis acid and Lewis base centers are simultaneously present in the boron-bridged thiophene-containing porphyrinogen 1 that has been synthesized in high yield. Its crystal structure reveals a nonplanar macrocycle; this and the colorless aspect suggest the absence of a delocalized π-electron system. R = NiPr .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…1.2−1.5. MALDI-TOF-TOF with benzo[ a ]pyrene/pyridine as the matrix showed peak patterns that correspond predominantly to linear polymers with the expected −Th 2 B(Ar)− repeating unit and bithiophene end groups (Figure ) . This indicates that the polymerization is not limited by solubility but rather by a small amount of destannylated bithiophene, which may form in the presence of trace amounts of protic acids.…”
mentioning
confidence: 97%
“…1.2−1.5. MALDI-TOF-TOF with benzo[ a ]pyrene/pyridine as the matrix showed peak patterns that correspond predominantly to linear polymers with the expected −Th 2 B(Ar)− repeating unit and bithiophene end groups (Figure ) . This indicates that the polymerization is not limited by solubility but rather by a small amount of destannylated bithiophene, which may form in the presence of trace amounts of protic acids.…”
mentioning
confidence: 97%
“…In addition, the unusual electronic properties of conjugated organoborane oligomers and polymers that result from p-π overlap of the empty p-orbital on boron with π-conjugated organic groups continue to fascinate researchers as they suggest potential applications in optoelectronic devices . However, although several reports on boron-containing macrocycles have appeared in the literature, in most cases the Lewis acidity of boron is low due to π-overlap with amino or alkoxy substituents or the borons are tetracoordinate, and thus no significant electron delocalization is present . Herein we describe a rational approach to hitherto unprecedented bora-cyclophanes that feature multiple highly electron-deficient organoborane moieties as an integral part of the ring system and thus constitute the first “charge-reverse” analogues of electron-donating macrocycles such as porphyrins, phthalocyanines, calixarenes, oligopyrrols, and recently introduced triarylamine-based aza-cyclophanes. , We also discuss the effect of cyclization on optical and electronic characteristics and present preliminary results on the complexation of anions, which can act as a stimulus to turn the electron-deficient macrocycle into an electron-rich one.…”
mentioning
confidence: 99%
“…They are also related to tetrameric thienylboranes, introduced by Siebert et al and referred to as "tetrathiaporphyrinogens", but the latter contain electron-donating amino groups on boron that limit the electron-deficient character. [21] More recently, He et al reported 3,3'-borylated bithiophene dimers (dibora [10]annulenes) that could be isolated and crystallographically characterized, and related studies were disclosed subsequently by Helten et al [12m,22] The reasons for the wider molecular weight distribution and observation of cyclic species with additional thienylene units for PFB3T'-B remain not well understood. Given that the brominated monomer used in the synthesis of PFB3T'-B was prepared from the respective iodinated species it is possible that the presence of traces of an iodo species in the polymerization mixture influenced the polymerization process.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%